Implementasi Linear Programming Untuk Efisiensi Biaya Operasional Produk Sayuran Hidroponik Di Kecamatan Semen Kediri - Cindy Nuraini; Edwin Agus; Zaenul Muttaqien (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to optimize hydroponic vegetable production strategies at KEA Farm through the application of the Linear Programming method using a quantitative descriptive approach. The main focus of the research is to determine the optimal production combination between lettuce and mint leaves by considering resource constraints, including working time (180 hours per month), land capacity (100 units), and production cost (Rp 110,000). Data were collected through observation, interviews, and documentation studies, and were then analyzed using the graphical method and validated with manual calculations. The results indicate two optimal production strategies. The first strategy involves the single production of 22 units of lettuce, generating a maximum profit of Rp 66,000 per cycle, with 100% cost utilization, 24% working time utilization, and 22% land utilization. The second strategy is product diversification, combining 16 units of lettuce and 5 units of mint leaves, resulting in a profit of Rp 53,000. However, this approach provides long-term strategic advantages through market expansion and reduced dependency on a single commodity. The implementation of the Linear Programming model proved effective in enhancing resource allocation efficiency and supporting production decision-making. This research offers practical contributions for micro agribusiness actors by providing an easily applicable analytical approach, as well as academic contributions through the integration of graphical visualization methods and mathematical precision in optimizing small-scale hydroponic production.